GEOTHERMAL ENERGY OF THE REPUBLIC OF SRPSKA AND HYDROCHEMICAL ASPECTS OF ITS EXPLORATION AND EXPLOITATION - Stevanović, A.; Jolović, B. (Journal of Engineering & Processing Management, 2015)
One of the most used renewable energy sources worldwide is geothermal energy. It represents the heat, originated by natural processes happen in the Earth interior. The hot springs phenomena are the most frequent natural manifestation of geothermal activity. Geothermal potentiality of some area can be estimated based on geothermal gradient. Geothermal gradient is a conductive terrestrial parameter that represents the degree of increasing of the Earth temperature vs. depth. It is usually expressed in ⁰C/m or ⁰C/km. Different areas have different thermal gradients and thus different geothermal potential. Generally, higher geothermal gradients correspond to areas containing more geothermal energy. Geothermal characteristics of the territory of the Republic of Srpska are closely related to its complex geological setting. It is the reason why geothermal characteristics are different from area to area. Higher geothermal potentiality is recognised in the northern parts of the entity, in the first order in Semberija, Posavina and Banja Luka regions. The use of geothermal energy with different fluid temperatures can be considered throughthe Lindal diagram, who firstly proposed acomprehensive scale with appropriate temperatures for different uses. High temperature fluids are mostly used for electricity production and moderate and low temperature fluids for the direct use.Despite the fact that the territory of the Republic of Srpska has favourable geothermal properties, utilization of this kind of renewable energy resource is inadequate. Especially indicative are data about the use of geothermal energy by heat pumps (in bad sense) in comparison with praxis of developed countries. Chemical composition of thermal waters plays very important role and can be used in its exploration stage, for analyses of possibility of its use and for prediction of exploitation effects, as well. This kind of renewable energyresource, highly ecologically recommended, must be considered more seriously in the future in the Republic of Srpska. Furthermore, it must be put into the energy strategic documentsin appropriate manner.